Consumer Behavior Analysis on Online and Offline Shopping During Pandemic Situation - Miguel Córdova Espinoza; Varsha Ganatra; Kiran Prasanth; Rupesh Sinha; Corina Elena Ochoa Montañez; Kolhe Mayur Sunil; Rishikaysh Kaakandikar (AIBPM Publisher, 2021)
Shopping has undergone a paradigm shift as a result of technological influence, with most consumers preferring online purchasing to traditional physical store shopping. The current pandemic scenario has resulted in a shift in customer spending patterns both online and offline. This paper identifies and analyses customers’ behavior towards online and retail shopping based on various factors affecting their behavior on which mode of shopping most they prefer during the pandemic situation. Primary data was used and a structured questionnaire was utilized to obtain the data. An online survey was conducted to collect from 200 heterogeneous kinds of people. The data collected were subjected to frequency analysis, Chi-square test, and Cronbach’s Alpha Test. IBM Statistical Package for Social Sciences (SPSS v23) was used for analyzing the data. The results revealed that among the various technological factors the proficiency rate of respondents utilizing, the internet has shown a significant impact on the consumers’ preference towards the mode of shopping. Factors like quick product information, a wider choice of products, better prices and discounts highly influence the consumers to opt for online shopping, whereas faster delivery time and product quality reliability and accuracy influence the consumers to choose offline shopping.